1987
DOI: 10.1073/pnas.84.11.3560
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside triphosphate-dependent DNA-binding properties of mos protein.

Abstract: We have previously shown that the mos gene product, p40f°, produced in Escherichia coli binds ATP and has ATPase activity. In the present study, we investigated the DNA-binding properties of p4011S and two mos deletion mutant proteins. Nitrocellulose blot protein-DNA binding assaysshowed that p40otm binds DNA in the presence of Mg2+-ATP and certain other nucleoside triphosphates. Ninety percent of the p40'°"-bound DNA is dissociated if the complex is washed in the presence of 1 M NaCl or in the absence of ATP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These studies have shown that it is a soluble cytoplasmic protein (21) with serine/threonine kinase activity (17,18). It also has been shown that the product of v-mos is an ATPase (19) and has ATP-dependent nucleic acid-binding activity (22). Both vmos and the mouse c-mos, designated Mos, have equivalent biological transforming activities in NIH 3T3 cell transfection assays (23).…”
mentioning
confidence: 99%
“…These studies have shown that it is a soluble cytoplasmic protein (21) with serine/threonine kinase activity (17,18). It also has been shown that the product of v-mos is an ATPase (19) and has ATP-dependent nucleic acid-binding activity (22). Both vmos and the mouse c-mos, designated Mos, have equivalent biological transforming activities in NIH 3T3 cell transfection assays (23).…”
mentioning
confidence: 99%
“…A number of studies have shown a perfect correlation between the protein kinase activity of both c-mos and v-mos and their biological function, either as tumor-causing proteins or as regulators of maturation-promoting factor (MPF) in oocytes and eggs [I , . Two other biochemical activities, namely an ATPase and a nucleic acid-binding activity, have been attributed to v-rnos [12,13]. However, the physiological relevance of these activities is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The v-mos protein, expressed in bacteria as a fusion protein, was found to have an ATP-dependent DNA-binding activity and an ATPase activity (22,23). This fusion protein, although expressed in large amounts in bacteria, was insoluble, requiring 8 M urea treatment for biochemical studies.…”
mentioning
confidence: 99%